THE CORRELATION BETWEEN STUDENTS’ MOTIVATION AND THEIR SPEAKING ACHIEVEMENT AT SENIOR HIGH SCHOOL 4 KENDARI - Anggraini, Desy; Kamaluddin, Kamaluddin; Siam, Siam (Universitas Halu Oleo, 2020)
The objective of this study was to determine the correlation between the students‟ motivation and their speaking competence at grade 11 of Senior High School 4 Kendari. The design of this study was quantitative research and the population was all grade 11 students at Senior High School 4 Kendari with the total numbers of students was 620 students. The sample of this study was class XI MIA 7 (36 students). The instrument of this study were questionnaire and students‟ speaking score. The researcher collected the data by using questionnaire adapted from Sun (2009) as the data of students‟ motivation and final speaking score to get data about students‟ speaking achievement. To analyze the data, the researcher used descriptive statistic to view the students‟ speaking achievement and their motivation based on five categories are; very low, low, medium, high, and very high. The result of this study showed that students‟ speaking achievement was mostly categorized in good criteria. It also showed that the students were highly motivated to learn speaking English by using video blog. The result of inferential statistics analysis showed that there was a significant correlation between students‟ motivation and their speaking achievement at grade 11 of Senior High School 4 Kendari. It was proved by the result of product moment correlation (rxy = 0.487), which was higher than r-table = 0.329.It means that motivation and achievement had a positive correlation.